The Epidemiology And Bacteriology Of Leptospiral Infection In Two Selected Cattle Farms In Peninsular Malaysia - Chumponbunchorn, Kumlung (1991)

(untitled)
A serological survey of cattle on two selected farms in Malaysia revealed that 87.7 percent (150/171) of the animals examined had leptospiral antibodies. Sixty percent of the positive sera had titres to two or more serovars. serovar australis was found to be the most frequent Overall, serovar affecting the animals in these two farms. Amongst the three age groups of cattle, the year ling group h ad the highest prevalence (62/64) of infection. A bacteriological survey of cattle on the two farms revealed 11. 5 percent (13/113) of the animals were leptospiruric. Almost all of the isolates (12/13) were isolated from the yearling group. The isolates belonged to either the Sejroe or Pomona serogroup. Representative isolates have been sent to the Leptospirosis Reference Laboratory in Brisbane, Australia for definitive identification.